0 \\\\2^{\sqrt{x}-1 }=m^{2}\\\\3m^{2}-8m+4=0\\\\D=(-8)^{2}-4*3*4=64-48=16=4^{2}\\\\m_{1}=\frac{8+4}{6}=2\\\\m_{2}=\frac{8-4}{6}=\frac{2}{3}" alt="3*2^{\frac{x-1}{\sqrt{x} +1} }-8*2^{\frac{\sqrt{x}-1 }{2} }+4=0\\\\3*2^{\frac{(\sqrt{x} -1)(\sqrt{x}+1) }{\sqrt{x}+1 } }-8*2^{\frac{\sqrt{x}-1 }{2} }+4=0\\\\3*2^{\sqrt{x}-1 }-8*2^{\frac{\sqrt{x}-1 }{2} }+4=0\\\\2^{\frac{\sqrt{x}-1 }{2} }=m,m>0 \\\\2^{\sqrt{x}-1 }=m^{2}\\\\3m^{2}-8m+4=0\\\\D=(-8)^{2}-4*3*4=64-48=16=4^{2}\\\\m_{1}=\frac{8+4}{6}=2\\\\m_{2}=\frac{8-4}{6}=\frac{2}{3}" align="absmiddle" class="latex-formula">
Ответ : 9